MENA Shares Global Knowledge on Procurement under Public Private Partnerships - Lipson, Rachel; Ismail Ali, Nazaneen; Al-Kazzaz, Ala (World Bank, Washington, DC, 2015)
This MENA K&L Quick Note highlights the key lessons learned from the workshop entitled: Procurement Under Public private Partnerships (PPP): A Learning Event for the Water and Energy Sectors, held in Beirut, Lebanon on October 13-15, 2014. The event was organized by the Governance Global Practice Team at the World Bank Office in Beirut in coordination with the Public-Private Partnership Cross Cutting Solutions Area (GPCDR-PPP-CCSA). The event provided a platform to expose clients to best practices on PPP procurement, particularly in projects, sectors, and countries with upcoming PPP operations, as well as in countries that are exploring the possibility of utilizing PPP arrangements and are interested to learn more about the approach and the legal framework to support it.